Examining the relationship between conspiracy theories and COVID‐19 vaccine hesitancy: A mediating role for perceived health threats, trust, and anomie?. Issue 1 (10th December 2021) - McCarthy, Molly; Murphy, Kristina; Sargeant, Elise; Williamson, Harley
Abstract: The COVID‐19 pandemic has led to an upswing in conspiracy theory beliefs, which creates challenges for effectively countering the pandemic, with higher rates of COVID‐19 vaccine hesitancy found among conspiracy theorists. Research suggests health risk perceptions, trust in government and anomie may mediate the relationship between COVID‐19 conspiracy theory beliefs and vaccine hesitancy. However, the mediating role of trust in government and anomie on vaccine hesitancy have not been empirically examined in the context of COVID‐19, and it is not clear whether different conspiracy theories have distinct mediational pathways to vaccine hesitancy. The current study examines the extent to which perceptions of the health threat posed by COVID‐19, trust in government and anomie can explain the relationship between distinct COVID‐19 conspiracy theories and COVID‐19 vaccine hesitancy. Drawing on data from a national online survey of 779 Australian adults, a series of path analyses examining the influence of three distinct conspiracy theories on vaccination hesitancy revealed two key mediational pathways, which varied across conspiracy theory types. Anomie and perceptions of the health threat posed by COVID‐19 were the most common mediators of this relationship. Implications for COVID‐19 vaccine hesitancy and for conspiracy theory research are discussed.